Choosing the Right AI Model for Power Forecasting in Micro Gas Turbines: A Comprehensive Performance Study - Gazioğlu, Emrullah (Fırat University, 2026)
This study evaluates the power prediction performance of fourteen different Artificial Intelligence models (traditional Machine Learning and Deep Learning) using a dataset of 71,225 samples from a 3-kilowatt micro gas turbine. The GRU architecture achieved the highest accuracy (RMSE: 12.36; R²: 0.9997), while traditional models such as XGBoost offered competitive performance with significantly lower computational requirements (77.13 seconds versus 855.04 seconds training time). Our findings demonstrate that optimal model selection depends on specific operational requirements, with traditional ML models being preferable for real-time applications and DL architectures for scenarios requiring high accuracy.

Bu araştırmada, 3 kilowatt gücündeki bir mikro gaz türbininden elde edilen 71.225 örneklik veri seti kullanılarak, on dört farklı Yapay Zeka modelinin (geleneksel Makine Öğrenmesi ve Derin Öğrenme) güç tahmin performansı değerlendirilmiştir. GRU mimarisi en yüksek doğruluğu (RMSE: 12,36; R2: 0,9997) elde ederken, XGBoost gibi geleneksel modeller önemli ölçüde düşük hesaplama gereksinimleri (77,13 saniyeye karşı 855,04 saniye eğitim süresi) ile rekabetçi performans sunmuştur. Sonuçlar, optimal model seçiminin belirli operasyonel gereksinimlere bağlı olduğunu ve gerçek zamanlı uygulamalar için geleneksel Makine Öğrenmesi modellerinin, yüksek doğruluk gerektiren senaryolar için ise Derin Öğrenme mimarilerinin tercih edilmesi gerektiğini göstermiştir.
Mikro Gaz Türbinlerinde Güç Tahmini İçin Doğru Yapay Zekâ Modelinin Seçimi: Kapsamlı Bir Performans Çalışması
Keywords: Machine Learning Algorithms; Makine Öğrenmesi Algoritmaları